The Artistry Conception of K. Korsakas - Skeivys, Rimantas (Problemos, 1983)
The artistry conception of K. Korsakas, an outstanding representative of Lithuanian Marxist aesthetics, is analysed for the period of 1920-1930. Considering the truthfulness of an art work as its principal criterion, K. Korsakas spoke out for a progressive approach and realism in literature, fought against purely aesthetic tendencies in the development of art. Nevertheless, the gnoseological trend of his conception is supplemented by the principles of artistry, basing on the formal aspect of art. Side by side with the truthfulness, K. Korsakas put forward such criteria of artistry as unity, simplicity, clarity, liveliness, genuineness in a work of art.